Anxiety relief for teens : essential CBT skills and mindfulness practices to overcome anxiety and stress - Galanti, Regine (Zeitgeist, 2020)
". . . teaches [teenagers] how CBT-based skills and mindfulness techniques can help . . . manage . . . anxiety and reverse negative patterns"--OCLC.